Sci-Hub and medical practice: an ethical dilemma in Peru - Bendezú Quispe, Guido (2016)
Sci-Hub is a pirate repository of scientific papers launched in 2011, and currently hosts more than 46 million articles. Thousands of people use this repository every day to access information, reaching more than 200 000 daily downloads of scientific articles that they would otherwise have to buy.